DILEMA DETERMINISME MANUSIA: Sebuah Perjalanan Reflektif Sains - Surjani Wonorahardjo (Litbang STFT Widya Sasana Malang, 2002)
The development of science and technology cannot be excluded from the human thinking in modern world. One of the major problem which echo comes and goes along the time is the what so called